Carcass Characteristics and Qualitative Meat Traits of the Padovana Breed of Chicken - Marchi, M. De; Cassandro, M.; Lunardi, E.; Baldan, G.; Siegel, P.B. (International Journal of Poultry Science, 2005)
The aim of this study was to describe meat quality and carcass characteristics of the Padovana breed of chicken. The Padovana chicken is a historical fancy breed found in the Veneto region of Italy and produces meat that is typical to some local markets. The experiment reported here involved 60 chickens reared in an organic production system where housing was an indoor pen with access to a grass paddock. Experimental chicks were randomly selected from May 17 and 24, 2001 hatches and slaughtered at 150 and 180 days of age, respectively. Meat from 30 chickens (16 males and 14 females) from each slaughter age was stored for subsequent analysis of breast and thigh meat quality. Males were consistently heavier then females for live; without blood and feathers; eviscerated with head; neck, and legs; carcass; breast; and right thigh weight. There were no differences between males and females for chemical composition of the breast except for percentages of dry matter and ash (female > male). Generally, overall weights were greater at 180 then 150 days of age, whereas there was no difference between ages for breast chemical composition except for % protein (180 > 150). The breast and thigh had a low value of brightness and a distinctive blue meat color. The fatty acid profile of the breast consisted of a high percentage of polyunsaturated fatty acids. There were no differences between sexes for fatty acids, except for C16:0, C18:3w3 (female > male) and C18:1w7t, C20:4w6 (male > female).